JAKTV Local Broadcast Media Strategy in Maintaining Existence in the Digital Era - Deana Ratnamaya; Yasir Yasir; Chelsy Yesicha (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2024)
JAKTV is a local television station in Jakarta. The presence of various new broadcast media willcertainly add competitors and make people's tastes begin to change. In this regard, JAKTV must beable to plan and carry out various strategies to be able to adapt and transform in order to continueto exist and be able to compete in the current era. This research aims to identify how JAKTV'sstrategy in maintaining their existence as local television, using the Niche (Media Ecology) theoryby Dimmick and Rothenbuhler. The method used in this research is a qualitative approach and datacollection techniques are by interview, observation, and collecting documents related to theresearch. The results of this study indicate that JAKTV as a local Jakarta television station inmaintaining their existence is by carrying out strategies including, planning marketing activities toget advertisements by strengthening their brand to gain the trust of the public and consumers, aswell as providing good service and compliments to clients. Conducting audience segmentation bygrouping based on geographic, demographic, and psychological audiences and positioning bystrengthening an image as a local Jakarta television. Conducted programme planning, productionand partnership, designed programme execution using the “day parting" method, and monitoredand evaluated performance to develop future plans.